Evaluating the effects of behavior change training on the knowledge, confidence and skills of sport and exercise science students - James Matthews; Amanda M. Hall; Alison Keogh (BMC, 2020)
Abstract Background Behavior change interventions have the potential to have a transformative effect on the health of populations. Allied health professionals have a key role to play in delivering these interventions. However, traditionally undergraduate allied health professional programs have not had a behavior change focus. The aim of this study was to assess the effectiveness of a training program on sport and exercise science students' knowledge, confidence and skills in the provision of behavior change support. Method A mixed method convergent design was used to address the research question. Fifteen sport and exercise science students took part in a training program consisting of seven 90-min weekly face to face group sessions. Student satisfaction with training methods was assessed. Pre-to-post training changes in students' confidence and knowledge in the provision of behavior change support was evaluated. Delivery of behavior change support was assessed by an audio recorded role-play rated by an expert using the Health Care Climate Questionnaire, and an adapted version of the Communication Evaluation in Rehabilitation Tool. Students also completed a reflective assignment. Results Students were satisfied with the training. There were increases in students' confidence and knowledge of certain behavior change components post-training but not behavior change techniques. Students delivered behavior change support in a broadly needs supportive manner. The reflective assignment showed that students found particular behavior change strategies difficult to implement. Conclusion It is feasible to train undergraduate students in particular components of behavior change support. Academic institutions should embed behavior change training into the allied health professional curriculum to ensure graduates are job ready with the knowledge, confidence and skills to support health related behavior change within the wider health system.